2021
DOI: 10.1002/cbin.11710
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro cell model to study microglia activation in diabetic retinopathy

Abstract: Microglial activation has been studied extensively in diabetic retinopathy. We have previously detected activation and migration of microglia in 8‐week‐old diabetic rat retinas. It is widely acknowledged that microglia‐mediated inflammation contributes to the progression of diabetic retinopathy. However, existing cell models do not explore the role of activated microglia in vitro. In this study, microglia were subject to various conditions mimicking diabetic retinopathy, including high glucose, glyoxal, and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…DM is also associated with a gradual reduction of the microglial reactivity to brain injury induced by photoablation of the cerebral vessels. Our results are consistent with data suggesting that DM induces microglial activation and its dysfunction 11 , 13 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…DM is also associated with a gradual reduction of the microglial reactivity to brain injury induced by photoablation of the cerebral vessels. Our results are consistent with data suggesting that DM induces microglial activation and its dysfunction 11 , 13 .…”
Section: Discussionsupporting
confidence: 93%
“…There is growing evidence that DM-related chronic inflammation can activate microglia, the resident immune cells of the central nervous system (CNS) 10 12 . In vitro studies have shown that under chronic hyperglycemia, microglia become activated showing enlarged cell bodies, enhanced migration, and phagocytosis as well as increased production of pro-inflammatory factors 10 , 13 , 14 . However, the exact contribution of microglia to DM-related abnormalities of brain functions remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…DM is associated also with gradual reduction of the microglial reactivity to brain injury induced by photoablation of the cerebral vessels. Our results are consistent with data suggesting that DM induces microglial activation and its dysfunction [11,13].…”
Section: Discussionsupporting
confidence: 93%
“…There is growing evidence that DM-related chronic in ammation can activate microglia, the resident immune cells of the central nervous system (CNS) [10][11][12]. In vitro studies have shown that under chronic hyperglycemia, microglia became activated showing enlarged cell bodies, enhanced migration and phagocytosis as well as increased production of pro-in ammatory factors [10,13,14]. However, the exact contribution of microglia to DM-related abnormalities of the brain functions remain poor understood.…”
Section: Introductionmentioning
confidence: 99%
“…To address the metabolic features of ARM with immune response, microglia cell line BV2 with hypoxia stimulation was established to mimic ARM in DR. Because the tissue hypoxia is associated with diabetes mellitus and responsible for DR development (11). Hypoxia-induced BV2 activation is manifested by increased cell proliferation, migration, phagocytosis, and increased proinflammatory factor production (1,42). Here, the microglia activation was confirmed by the evidence of significant differential expression of IL-1b at mRNA and protein levels (Figures 4A, B).…”
Section: Hypoxia-induced Bv2 Microglia Activation With Metabolic and ...mentioning
confidence: 79%